Low Serum Ferritin Level: A Risk Factor of Simple Febrile Seizures– A Hospital-Based Case-Control Study (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Febrile seizure (FS) is the single most common seizure type in children younger than 5 years. The age for peak incidence of febrile seizure is 14 to 18 months, which overlaps with that of iron deficiency anemia.Objectives: The purpose of this study was to explore the association of serum ferritin and iron deficiency anaemia with simple febrile seizures.Methods: In this case-control study 50 patients with febrile seizure were evaluated for iron deficiency anaemia by estimation of Hemoglobin%, MCV, MCH, RDW, and serum ferritin. The control group consisted of 50 febrile children of the same age group without convulsion. Data were recorded in case record form and all the outcomes were recorded.Results: In this study, the mean age of the patients was 20.48 ± 13.79 (range: 6-60) months. In the case group, the mean (± SD) Serum Ferritin level was 52.54 ± 52.64 µg/L and in the control group, the mean (± SD) S. Ferritin level was 87.40 ± 75.74 µg/L. In the case group, 46% of patients had low ferritin level and in the control group, 24% of patients had low ferritin level. Iron Deficiency Anaemia (IDA) was found among 26% of children in the case group and 14% in the control group.  A statistically significant difference was found regarding mean S. Ferritin level and ferritin status between the case and control group.  (Odds ratio 0.002 and 2.698)  But, in the case of IDA, there was no statistically significant difference observed between the groups.Conclusion: A low ferritin level was associated with an increased risk of febrile seizures. Therefore, in children with febrile seizures, clinicians should be concerned about ferritin status even at normal hemoglobin levels.J Bangladesh Coll Phys Surg 2024; 42: 139-143